2014
DOI: 10.1080/17518253.2014.969786
|View full text |Cite
|
Sign up to set email alerts
|

Environmentally green approach to synthesize azo dyes based on 1-naphthol using nano BF3·SiO2under solvent-free conditions

Abstract: A series of azo dyes were efficiently synthesized by mixing aromatic amines and NaNO 2 in the presence of nano silica supported boron trifluoride (nano BF 3 ·SiO 2 ) and then diazo coupling with 1-naphthol under solvent-free conditions at room temperature. The present methodology has proven to be simple, rapid, environmentally benign, green, and cost-effective compared with previous synthetic methods. Also, by using this procedure, aryl diazonium salts supported on nano BF 3 ·SiO 2 were very stable to be kept … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…TiO 2 is one of the most popular and widely studied semiconducting photocatalytic materials for reduction of nitroarenes. ,, In the pioneering and early studies by Mahdavi et al and by Ferry and Glaze, a wide range of nitro-functionalized aliphatic and aromatic nitro compounds were photoreduced over commercial TiO 2 . The photoreduction mechanism and the importance of hole scavengers were realized in the early investigations. Nitroarenes reduction is a stepwise multi-electron–proton reduction, as can be seen in Figure .…”
Section: Photocatalytic Reduction Of Nitroarenesmentioning
confidence: 99%
“…TiO 2 is one of the most popular and widely studied semiconducting photocatalytic materials for reduction of nitroarenes. ,, In the pioneering and early studies by Mahdavi et al and by Ferry and Glaze, a wide range of nitro-functionalized aliphatic and aromatic nitro compounds were photoreduced over commercial TiO 2 . The photoreduction mechanism and the importance of hole scavengers were realized in the early investigations. Nitroarenes reduction is a stepwise multi-electron–proton reduction, as can be seen in Figure .…”
Section: Photocatalytic Reduction Of Nitroarenesmentioning
confidence: 99%
“…As a result, the development of a methodology for conversion to harmless nitroamines has become a top priority and an essential focus for environmental protection [29]. However, the catalytic reduction of nitroaromatics is considered an essential chemical reaction in the fabrication of many compounds, including dyes, the pharmaceutical industry, and the production of pesticides [30][31][32][33]. Although many studies have been reported extending more environmentally friendly methods for the selective reduction of nitro compounds to their amino analogues [34, 35], Most of these methods have some limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we pay attention to 1-naphthols, one of the common groups of organic compounds used in the production of dyes [5,11,18,25,30,34,36,49,54] (including the green chemistry approach [6]), which have not been taken into account with regard to becoming the components of composite materials yet.…”
Section: Introductionmentioning
confidence: 99%